AN ANALYSIS OF LEXICAL AND CONTEXTUAL MEANING IN LEWIS CAPALDIâ€™S SONG LYRICS - Meirina Sulastri Belu; Christina Maya Iriana Sari (Universitas Katolik Widya Mandala Surabaya, 2021)
The research entitled â€œAn Analysis of Lexical and Contextual Meaning in Lewis Capaldiâ€™sSong Lyricsâ€. This research aimed to find out the lexical and contextual meanings,describing both meanings in each data, and classifying the types of context that are found ineach data. There were three songs as the object of the research taken from DivinelyUninspired to a Hellish Extentâ€™s album entitled â€œLeaving my Love Behind, Lost on You andHold Me While you Waitâ€. This research used the descriptive qualitative method since theresearcher analyzed and interpret Lewis Capaldiâ€™s song lyrics. Mansoer Patedaâ€™s theoriesare used in this research. The data were found in the form of words and phrases which havelexical and contextual meaning in song lyrics. The step to obtain the data was collectingsources of data from Lewis Capaldi songs taken from the internet. After that, the researcherread, selected, and listened to the song to understand the context of the song and analyzedthem based on research focuses. As a result of this research, the researcher found 33 datathat had lexical and contextual meaning. Then, from 33 data, there were five types of contextthat are found, such as mood context, situational context, purpose context, object context,and context of time. According to the results found, the situational context is the dominant inthis study since it shows someone's situation about his relationship.Keywords: semantics, lexical meaning, contextual meaning, Lewis Capaldi